2015
DOI: 10.1007/s00401-015-1474-4
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar c9RAN proteins associate with clinical and neuropathological characteristics of C9ORF72 repeat expansion carriers

Abstract: Clinical and neuropathological characteristics associated with G4C2 repeat expansions in chromosome 9 open reading frame 72 (C9ORF72), the most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia, are highly variable. To gain insight on the molecular basis for the heterogeneity among C9ORF72 mutation carriers, we evaluated associations between features of disease and levels of two abundantly expressed “c9RAN proteins” produced by repeat-associated non-ATG (RAN) translation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
108
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 98 publications
(122 citation statements)
references
References 43 publications
11
108
3
Order By: Relevance
“…S5C) were selectively detected in c9ALS fibroblasts. Consistent with previous findings in brain tissues from c9FTD/ALS patients (11), the abundance of poly(GP) proteins correlated with mRNA levels of C9orf72 variant 3 (Fig. S5G) but not of variant 1, variant 2 or total C9orf72 mRNA (Fig.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…S5C) were selectively detected in c9ALS fibroblasts. Consistent with previous findings in brain tissues from c9FTD/ALS patients (11), the abundance of poly(GP) proteins correlated with mRNA levels of C9orf72 variant 3 (Fig. S5G) but not of variant 1, variant 2 or total C9orf72 mRNA (Fig.…”
supporting
confidence: 92%
“…S1C). These data are consistent with the prior finding that the abundance of poly(GP) proteins correlate with levels of repeat-containing transcripts (11, 12). Importantly, deleting SPT4 in (GGGGCC) 40 -expressing yeast significantly decreased levels of RAN-translated poly(GP) (Fig.…”
supporting
confidence: 92%
“…While we were unable to examine correlations between CSF poly(GP) and repeat length in blood because repeat length data were not available, such an analysis would likely be complicated given the substantial variation in repeat sizes among various tissues from the same individual 33. Furthermore, a previous study has shown no association between CSF poly(GP) and repeat length in blood,14 and we observed no association between poly(GP) levels in the cerebellum or frontal cortex and repeat length in these regions 35. Nonetheless, examining associations between antemortem CSF poly(GP) and repeat size, poly(GP) levels, and levels of other DPR proteins in various neuroanatomical regions will be of interest when postmortem tissue becomes available from a suitable number of cases.…”
Section: Discussioncontrasting
confidence: 53%
“…Levels of soluble poly(GP) were measured using a previously described sandwich immunoassay using a poly(GP) antibody [21].…”
Section: Gp Immunoassaymentioning
confidence: 99%